PRODUCTIVE UTILIZATION OF ZAKAT, INFAK, AND ALMS FUNDS FROM MOSQUES FOR THE ECONOMIC EMPOWERMENT OF THE COMMUNITY IN MEDAN CITY: THE PERSPECTIVE OF AL-MASLAHAH AL-MURSALAH - Warohmah, Mawaddah; Azmy, Azmy; Nasution, Muhammad Syukri Albani (International Journal of Cultural and Social Science, 2025)
This research aims to analyze the productivity of zakat, infak, and ?adaqah (ZIS) in empowering the Muslim community’s economy; assess the effectiveness of its productive management; and examine it through the lens of al-Ma?la?ah al-Mursalah. This study employs a qualitative method with a descriptive–interpretative case study approach conducted at four mosques in Medan City, namely Asy-Syafi‘iyah Mosque, Al-Hidayah Mosque, Haji Maraset Mosque, and Nurul Islam Mosque. The findings reveal that productively managed ZIS can transform from a consumptive-charitable pattern into a sustainable socio-economic investment through the development of community-based enterprises, Islamic cooperatives, and mosque business units. From the perspective of al-Ma?la?ah al-Mursalah, this management model reflects a concrete form of public benefit in terms of ?if? al-m?l (protection of wealth), as it delivers socio-economic utility without contradicting the principles of Sharia. This study offers a theoretical contribution by integrating the concept of al-Ma?la?ah al-Mursalah into mosque-based Islamic philanthropy practices, as well as practical implications for advancing professional and empowerment-oriented governance of communal religious funds.